ChemInform Abstract: Gold‐Catalyzed Photoredox C(sp2) Cyclization: Formal Synthesis of (.+‐.)‐Triptolide. Issue 42 (September 2016) - Cannillo, Alexandre; Schwantje, Travis R.; Begin, Maxime; Barabe, Francis; Barriault, Louis
Abstract: The method is applied in the construction of compound (VI), a key intermediate in the total synthesis of (.+‐.)‐triptolide (VII).